An Examination of Policy Failures and Structural Issues in Nepalese Foreign Trade (1994–2024) (Voice: A Biannual & Bilingual Journal, 2025)
This paper analyses Nepal's foreign trade performance from 1994 to 2024, emphasising enduring structural and policy deficiencies that have perpetuated a chronic trade deficit. Despite economic liberalisation in the 1990s, Nepal's trade deficit rose 45 times (from $300 million to $13.5 billion), but exports remained stagnant at 10% of total trade. Critical challenges encompass geographic entrapment as a landlocked nation, remittance-reliant import dependency, ineffective trade agreements (e.g., SAFTA, Nepal-India Treaty), and inadequate industrial infrastructure. The paper highlights unequal advantages in bilateral agreements, exploitable weaknesses in Rules of Origin, and non-tariff barriers as significant obstacles. It also faults Nepal's inability to diversify exports beyond low-value items (e.g., carpets, textiles) or markets beyond India, which constitutes 65% of trade. Political instability, policy inconsistency, and the ramifications of Dutch Disease resulting from remittances further intensify trade challenges. The report proposes the Himalayan Trade Transition Framework, advocating for digital trade corridors, the establishment of export ecosystems, and deliberate regional involvement to disrupt this cycle.